Effect of Whitening Dentifrice on Micro Hardness, Colour Stability and Surface Roughness of Aesthetic Restorative Materials - Roopa, KB (J Clin Diagn Res, 2016)
INTRODUCTION: Whitening agents present in the novel whitening dentifrices may have deleterious effects over the aesthetic restorations. AIM: The present study evaluated the invitro effect of whitening dentifrice on micro hardness, colour stability and surface roughness on aesthetic restorative materials. MATERIALS AND METHODS: Forty specimens each of compomer and of composite were prepared using brass mould. Specimens were equally divided into 4 groups. Group I (20 disks of compomer are subjected to brushing with conventional tooth paste) Group II (20 disks of composite subjected to brushing with conventional tooth paste), Group III (20 disks of compomer subjected to brushing with whitening tooth paste). Group IV (20 disks of composite subjected to brushing with whitening toothpaste). Each group was further divided into two subgroups, where 10 sample were subjected for two weeks of brushing with respective tooth paste and other 10 were subjected for four weeks of brushing. For the evaluation of micro hardness, colour stability and surface roughness, micro hardness testing machine, spectrophotometer and surface testing machine were used respectively. Initial and final readings were taken for each specimen and difference obtained was subjected to statistical analysis. One-way ANOVA was used for multiple group comparison followed by post-hoc Tukey’s-test. The paried t-test was used for intra group comparison and unpaired t-test for comparing independent sample groups. RESULTS: The compomer and composite showed no significant difference in micro hardness either with conventional or whitening tooth paste both at two and four weeks. Although there was a highly significant colour change observed after using whitening tooth paste for both compomer and composite. Regarding surface roughness, there was a significant change in roughness in both conventional and whitening tooth paste with compomer and composite. However, whitening tooth paste had a significant change in surface roughness compared with conventional tooth paste. Roughness further increased at four weeks interval when compared to two weeks. CONCLUSION: Colour, surface-roughness and micro-hardness are the inherent properties of the aesthetic restorative materials. Use of whitening tooth paste will cause colour change and surface roughness of restorative material making it prone to deformation and also affects the clinical success of restoration.